An uncommon cause for hip pain and limping - Sahana Shetty; Samantha Sathyakumar; Nitin Kapoor; Thomas Vizhalil Paul (Journal of Family Medicine and Primary Care, 2015)
Slipped capital femoral epiphysis (SCFE) is characterized by displacement of the capital femoral epiphysis from the femoral neck. An 18-year-old male presented with left hip pain and a limping gait, following a trivial trauma. Radiological examination revealed bilateral SCFE. Clinically and biochemically, he had features of hypopituitarism. His prolactin levels were high and magnetic resonance imaging (MRI) scan showed a pituitary macroadenoma, suggesting a diagnosis of macroprolactinoma causing hypopituitarism and presenting as SCFE. He was started on dopamine agonist cabergoline as well as thyroxine and glucocorticoid replacement treatment. He was also scheduled for an orthopedic surgical procedure for his SCFE.